Integration of Human Factor and Artificial Intelligence in Customer Relationship Management Practices in Retail Coffee Sector in the UAE - Singh, Iqwinder Jeet (Digital Repository of Theses, 2025)
Introduction The UAE coffee retail sector have been growing at a rapid pace that provides an opportunity for businesses to grow. There has been a prevalent use of technologies such as AI, but the role of human interaction cannot be undermined in the coffee retail sector. Considering this the research seeks to explore “Integration of human factor and artificial intelligence in customer relationship management practices in retail coffee sector in the UAE3” Methodology The research has adhered to a qualitative approach by considering the philosophy of interpretivism. The section has demonstrated that the use of deductive research approach ensures theoretical perspectives can be used to validate the findings. Data was collected from 50 participants and the collected responses have been interpreted using graphical analysis method. The researcher has also ensured that protocols related to reliability and validity has been followed and ethical standards have been maintained by providing rights to the participants and safeguarding their identity. Findings and Discussion From the section it has been found that the behaviour of the consumers in the UAE coffee sector is complex and diverse. A range of customer prefer higher AI interaction while human AI is also preferred by most of the customers. It is seen that when the customers are made to use more AI it can help their experience through fast and convenience orders. AI also allows better customer relationship management by faster query solving. Conclusion The chapter of the study has concluded the findings and provided recommendations along with future scope of study. All four objectives of the study have been met while it has been recommended that a balance between AI and human interaction is maintained so that optimal benefits can be acquired by the coffee retailers of the UAE.